Three weeks of detraining does not decrease muscle thickness, strength or sport performance in adolescent athletes - Gavanda, S.; Geisler, S.; Quittmann, O. J.; Bauhaus, H.; Schiffer, T. (International Journal of Exercise Science, 2020)
The purpose of this study was to examine the effects of detraining following a block (BLOCK) or daily undulating periodized (DUP) resistance training (RT) on hypertrophy, strength, and athletic performance in adolescent athletes. Twenty-one males (age = 16 ± 0.7 years; range 15-18 years) were randomly assigned to one of two 12-week intervention groups (three full-body RT sessions per week): BLOCK (n = 9); DUP (n = 12). Subsequently a three-week detraining period was applied. Body mass, fat mass (FM), fat-free mass (FFM), muscle mass, muscle thickness (rectus femoris, vastus lateralis and triceps brachii), one-repetition maximum squat and bench press, countermovement jump (CMJ), peak power calculated from CMJ (Ppeak), medicine ball put distance, and 36.58m sprint were recorded before and after RT as well as after detraining. BLOCK and DUP were equally effective for improvements of athletic performance in young athletes. Both groups displayed significantly (Rho = 0.05) higher values of all measures after RT except FM, which was unchanged. Only FM increased (p = 0.010; ES = 0.14) and FFM decreased (p = 0.018; ES = -0.18) after detraining. All other measurements were unaffected by the complete cessation of training. Values were still elevated compared to pre-training. Linear regression showed a strong correlation between the percentage change by resistance training and the decrease during detraining for CMJ (R² = 0.472) and MBP (R² = 0.629). BLOCK and DUP RT seem to be equally effective in adolescent athletes for increasing strength, muscle mass, and sport performance. In addition, three weeks of detraining did not affect muscle thickness, strength, or sport performance in adolescent athletes independent of previous resistance training periodization model used.